Exploring the Attitudes, Perceived Value, and Repurchase Intention of the Elderly Towards Green Restaurants - Hsu-Hua Lee; Pao-Yuan Huang (Technium Social Sciences Journal, 2024)
This study investigates the attitudes, perceived value, and repurchase intentions of the elderly population towards green restaurants. With the increasing proportion of the elderly in Taiwan, their dietary needs have become more refined, focusing more on health and nutritional value. Consequently, restaurants offering healthy, nutritious, and environmentally conscious food choices are likely to be favored by this demographic. The social needs of the elderly population are also a consideration; restaurants that provide a healthy, environmentally friendly, and relaxed environment may become one of their options for social interaction, which is beneficial for maintaining mental health and quality of life. The results indicate a positive relationship between consumers’ attitudes towards the restaurant, perceived value, and repurchase intention. Consumers’ attitudes and perceived values towards green restaurants significantly impact their repurchase intentions. Additionally, consumers’ willingness to revisit is also influenced by the perceived value. Overall, this study fills the gap in research related to green restaurants and specific age groups in the catering industry and provides references for green restaurant operators in developing potential consumers and marketing strategies.